Legs bśad dad paʼi mdzes rgyan źes bya ba bźugs so : brjod bya dbaṅ po rno rtul gyi dad pa skye tshul - Dpal-ldan-grags-pa, Blo-gliṅ Dge-bśes (Paṇ-chen Bsod-nams-grags-pa literature series ;, 1979)
Exposition of the concepts of perfect wisdom (Madhyamakā) philosophy in different schools of Buddhist philosophy; viewpoint of the Gelukpa sect.